The International Law of Migrant Smuggling, Anne T. Gallagher et Fiona David - Ouedraogo, Awalou (Refuge: Canada's Journal on Refugees, 2014)
The International Law of Migrant Smuggling Anne T. Gallagher et Fiona David Cambridge University Press, 2014: ISBN 987-1-107-01592-0 (Hardback), 783 p.